An Exploration of Data Interoperability for GDPR - O'Sullivan, Declan; Lewis, David (My University, 2018)
The General Data Protection Regulation (GDPR) specifies obligations that shape the way information is collected, shared, provided, or communicated, and provides rights for receiving a copy of their personal data in an interoperable format. The sharing of information between entities affected by GDPR provides a strong motivation towards the adoption of an interoperable model for the exchange of information and demonstration of compliance. This article explores such an interoperability model through entities identified by the GDPR and their information flows along with relevant obligations. The model categorises information exchanged between entities and presents a discussion on its representation using existing standards. An investigation of data provided under the Right to Data Portability for exploring interoperability in a real-world use-case. The findings demonstrate how the use of common data formats hamper its usability due to a lack of context. The article discusses the adoption of contextual metadata using a semantic model of interoperability to remedy these identified shortcomings.
PUBLISHED
Keywords: Data format; Data standards; GDPR; Interoperability; Semantics; Digital Engagement; Knowledge and data engineering